Biology of Gram Blue Butterfly, Euchrysops Cnejus (Fabricius) (Lycaenidae: Lapidoptera) and its Relationship with the Phenology of Host-plant (Vigna Unguiculata: Fabaceae) (Journal of Bangladesh Academy of Sciences, 2015)
The biology of the gram blue butterfly, Euchrysops cnejus (Fabricius) (Lycaenidae: Lapidoptera) and its relationship with the phenology of host plant cowpea, Vigna unguiculata L. (Fabaceae) were studied. Eggs were reared under the laboratory conditions at 28 ± 20C and 74 ± 3% RH. The incubation period of the eggs found to be 2.33 ± 0.51 days, larval developmental period 14.65 ± 0.51 days, pre-pupal period 0.30 ± 0.04 day and pupal period 5.66 ± 0.51 days. The species took 22.94 ± 0.55 days for development from egg to adult under the laboratory condition. The length of 1st, 2nd, 3rd and 4th instar larvae was 3.66 ± 0.40, 6.16 ± 0.51, 12.16 ± 0.51 and 15.33 ± 0.40 mm, respectively. The pre-pupal length was 9.16 ± 0.61 mm and the pupal length was 9.08 ± 0.37 mm. The host-plant occurs in the field from February to July. The butterfly appeared in March. The coincidence of the gram blue butterfly to its host-plant occurred between April and early July. The oviposition behaviour, incubation and immature stages were found to be profoundly related with host plant-phenological phases.Journal of Bangladesh Academy of Sciences, Vol. 39, No. 2, 241-248, 2015